Pengembangan Media Pembelajaran Telegram Untuk Meningkatkan Kemampuan Menyimak Dan Berpikir Kritis Di Sekolah Dasar - Wadhono, Agus; Priyantoro, Yudha Budhi; Mu’minin, Moh. (Inovasi: Jurnal Diklat Keagamaan, 2023)
The development of this telegram learning media is based on the fact that students' listening and critical thinking skills are still lacking. This is due to the limitations of learning media in the delivery of Indonesian subject matter, especially in listening skills. With the development of this telegram learning media, it can help students learn easily. The purpose of this research and development is to determine the quality of the media in terms of practicality, validity and effectiveness of the media. The research method used by the researcher is Research and Development (R&D) with a model developed by Borg and Gall. Data collection techniques in this study used a questionnaire, pre-test and post-test results, validation sheets and observations. The results showed that the development process went through the stages of analysis, design, development, implementation and evaluation. As for the validity of the media, it shows that the results of the validation of the material experts get a score of 94.29, the results of the validation of the media experts get a score of 84.61 and the results of the validity by practitioners get a score of 95. The practicality of the media shows that the results of the teacher practicality questionnaire get a score of 95% and the results of the student practicality questionnaire obtained a score of 94.47%. The effectiveness of the telegram learning media got a score of 82.64. Based on the results of practicality, validity and effectiveness, it can be concluded that the practicality of the media is included in the very practical category, the validity of the media and materials is included in the very valid category, and the effectiveness of the media is included in the very good category.